2015
DOI: 10.4103/0970-9290.167632
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular canine index: A reliable predictor for gender identification using study cast in Indian population

Abstract: Study findings reveal that MCI can be used a reliable predictor for gender determination in Indian population and can form the basis of anthropologic and forensic investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
1
13
1
2
Order By: Relevance
“…When compared to the literature (Table 2), the present study reveals higher similarity with the North American and the previous Brazilian (COSTA et al, 2012) populations. However, in general the MD and BL dimensions obtained in the present study were smaller compared to others (JOFRÉ et al, 2009;BISHARA et al, 1989;YUEN et al, 1995;HATTAB et al, 1996;JAIN et al, 2011;SINGH et al, 2015).…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…When compared to the literature (Table 2), the present study reveals higher similarity with the North American and the previous Brazilian (COSTA et al, 2012) populations. However, in general the MD and BL dimensions obtained in the present study were smaller compared to others (JOFRÉ et al, 2009;BISHARA et al, 1989;YUEN et al, 1995;HATTAB et al, 1996;JAIN et al, 2011;SINGH et al, 2015).…”
Section: Resultscontrasting
confidence: 53%
“…In the Mexican population, all dimensions in males were larger for all tooth groups. Dental dimorphism expressed within larger teeth in males was also confirmed by Yuen et al (1995) within a Chinese population; Hattab et al (1996) within a Jordanian population; Yamaguto et al (2005) and Costa et al (2010) within Brazilian populations; Jofré et al (2009) within Spanish and Chilean populations; and by Jain et al (2011) and Singh et al (2015) within an Indian population.…”
Section: Introductionsupporting
confidence: 55%
“…Esses resultados são apresentados na tabela 2, onde destaca-se as médias encontradas. sistente à doença, à agressões externas, à sobrevivência a trauma pós-morte e sendo apontado como um dos indicadores mais confiáveis e válidos [8][9][10]11 .…”
Section: Discussionunclassified
“…com os resultados encontrados houve diferença significativa observada entre a distância inter-canina, largura do canino direito e esquerdo entre homens e mulheres, o dimorfismo sexual foi apontado sendo mais proeminente no canino esquerdo inferior permanente 10 .…”
Section: Discussionunclassified
“…Singh et al in a study found that the intercanine distance, right canine width, left canine width, right MCI and left MCI was found to be significantly higher in males than females. [ 28 ] Nonmetric features such as a distal accessory ridge, Carabelli's trait of upper molars, shovelling of upper central incisor, number of cusp in mandibular first molar can be used in sex determination. The distal accessory ridge in canine is more pronounced in male compared to female.…”
Section: Postmortem Dental Profilingmentioning
confidence: 99%